(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The textile industry plays a pivotal role in the global economy, and BRICS nations—Brazil, Russia, India, China, and South Africa—are among the leading contributors to this sector. This review aims to analyze the opportunities and challenges faced by these nations in textile trading, focusing on the unique advantages and obstacles each country encounters within the global market. BRICS nations collectively hold a significant share of textile production and export, leveraging their diverse resources, large labor forces, and cost-effective manufacturing capabilities. Opportunities arise from trade partnerships, evolving consumer preferences, and advancements in technology that enhance productivity and sustainability. However, the textile trade also faces challenges such as fluctuating international trade policies, environmental regulations, rising production costs, and increasing competition from non-BRICS countries. Additionally, the COVID-19 pandemic has disrupted supply chains, leading to shifts in demand and creating new hurdles for manufacturers and exporters. This review explores how BRICS nations are adapting to these challenges by investing in innovation, sustainable practices, and strengthening intra-BRICS trade relations. It also assesses how geopolitical tensions and economic disparities among these countries impact the overall competitiveness of their textile industries.